Academic and psychosocial characteristics of incoming college freshmen with autism spectrum disorder: The role of comorbidity and gender. Issue 6 (10th April 2019) - Sturm, Alexandra; Kasari, Connie
Abstract : There is a pressing need to better characterize the college‐bound population of individuals with autism spectrum disorder (ASD), as prior studies have included small samples, consisting of individuals who are either recruited due to diagnosis or are treatment seeking. As postsecondary institutions look to respond to the growing need for support services for individuals with ASD, insights derived from large, population‐based samples is a necessity. The current study included a sample of over 2000 incoming postsecondary students who self‐identified with ASD as a part of surveys distributed by institutions nationally. The impact of heterogeneity (gender, comorbid attention‐deficit/hyperactivity disorder [ADHD], and/or learning disability) on demographic characteristics, and psychosocial (psychological health, interpersonal self‐confidence) and academic (self‐regulated learning, intellectual self‐confidence) domains critical for success in postsecondary education were compared to a matched sample of students with ADHD or no diagnoses. College‐bound students with ASD broadly endorsed similar rates of ADHD, LD, and psychological disorder comorbidity to clinic‐referred samples, and were more similar than different from their typically developing peers. A comorbid diagnosis of ADHD was associated with greater academic disengagement. Females with ASD and those with any comorbid disorder were more likely to self‐report poorer psychological health. Findings revealed that self‐reported levels of functioning in critical domains differed by self‐reported comorbid disorders and gender. Findings have implications for targeted support service recommendations based on unique sources of heterogeneity (e.g., gender, presenting comorbid disorders) and are detailed in the current study. Autism Res 2019, 12: 931–940 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: College‐bound students with ASD feel academically competent; however feel less confident with their peers. Students with ASD and another diagnosis (e.g., ADHD, learning disability) and girls with ASD may be particularly at risk of experiencing poorer psychological health while enrolled in postsecondary education. Using this information, postsecondary institutions can provide more targeted support services to students with ASD enrolled in postsecondary education.